Tabloid city : a novel - Hamill, Pete, 1935-2020. (New York : Little, Brown and Co., 2011)
When a wealthy socialite and her secretary are found murdered in a stately West Village townhouse, a flurry of seemingly unrelated people spring into action. A reporter chases the story while a tabloid executive holds the presses, a ruined financer attempts to leave the country, a war veteran plots revenge, and a terrorist plans an attack.
Keywords: Socialites -- Crimes against -- Fiction; Murder -- New York (State) -- New York -- Fiction; New York (N.Y.) -- Fiction